The equation for exponential decay is given as y = a(1 - r)^x.
<u>Explanation:</u>
The formula for original exponential decay is y = ab^x.
The growth rate (r) is determined as b = 1 + r.
The decay rate (r) is determined as b = 1 - r.
y = ab^x (Where b = 1 - r)
y = a(1-r)^x
a represents the initial value
r represents growth or decay rate
x represents the number of time intervals that have passed.
<em>For example</em>
The population of Home Town is 2016 was estimated to be 35,000 people with an annual rate of increase of 2.4%.
The equation for decay factor y = 35000(1 - 0.024)^x
y = 35000(0.976). (where x = 1)
Answer:
pay rate £7.80
Step-by-step explanation:
28860 divide by 37 = 780
780 divided by 100 = 7.80
<span>$20/16=$1.25/candy bar
Candy bars cost $1.25 each </span>
Answer:
D 20 *1.10 * 1.05
Step-by-step explanation:
We have 19.8 tons of wheat. That is close to 20 tons
We increase by 9.8 percent. 9.8% is close to 10%
When we increase, that is 100% of what we had plus the increase, so we multiply by 100 +10% or 110%. In decimal form that is 1.1
20 *1.10
Then the next year we increase by 5.1%. That is close to 5%
We have 100% plus the 5% or 105%, which in decimal form is 1.05
We multiply what we had (20 *1.10) by 1.05
20 *1.10 * 1.05
This is the total amount we have